Neuroradiologic Evaluation of MRI in High-Contact Sports - McAllister, Derek; Akers, Carolyn; Boldt, Brian; Mitchell, Lex A.; Tranvinh, Eric; Douglas, David; Goubran, Maged; Rosenberg, Jarrett; Georgiadis, Marios; Karimpoor, Mahta; DiGiacomo, Phillip; Mouchawar, Nicole; et al. (Frontiers in Neurology, 2021)
Background and Purpose Athletes participating in high-contact sports experience repeated head trauma. Anatomical findings, such as a cavum septum pellucidum, prominent CSF spaces, and hippocampal volume reductions, have been observed in cases of mild traumatic brain injury. The extent to which these neuroanatomical findings are associated with high-contact sports is unknown. The purpose of this study was to determine whether there are subtle neuroanatomic differences between athletes participating in high-contact sports compared to low-contact athletic controls. Materials and Methods We performed longitudinal structural brain MRI scans in 63 football (high-contact) and 34 volleyball (low-contact control) male collegiate athletes with up to four years of follow-up, evaluating a total of 315 MRI scans. Board-certified neuroradiologists performed semi-quantitative visual analysis of neuroanatomic findings, including: cavum septum pellucidum type and size, extent of perivascular spaces, prominence of CSF spaces, white matter hyperintensities, arterial spin labeling perfusion asymmetries, fractional anisotropy holes, and hippocampal size. Results At baseline, cavum septum pellucidum length was greater in football compared to volleyball controls (p = 0.02, uncorrected). Within football at baseline, more years of prior football exposure were associated with more perivascular spaces (p = 0.03), and lower baseline Standardized Concussion Assessment Tool scores were associated with more perivascular spaces (p = 0.02) and a smaller right hippocampal size (p = 0.02). Conclusion Head impacts in high-contact sport athletes may be associated with neuroanatomical findings visible through radiological analysis, including increased cavum septum pellucidum length, increased perivascular spaces, and decreased hippocampal size.